THE EFFECT OF EDMODO BASED BLENDED LEARNING ON ACCOUNTING LEARNING OUTCOMES VIEWED SELF REGULATED LEARNING - Satiti, Abidah Dwi Rahmi; Fibriyanti, Yenni Vera (UNIVERSITAS PAKUAN, 2021)
The objective of this research was to investigate the difference effect between the Edmodo - Based Blended Learning and the conventional learning on accounting learning outcomes viewed self regulated learning. This research was an quasi experimental with nonequivalent pretest posttest control-group design. The population of research was the students in semester 4 of classes A, B, and C. The research sample was taken 2 classes, namely class B and class C. The data were analyzed by using the two-way analysis of variance and was continued with the Scheffe test. The findings showed that: (1) there was a difference effect between the Edmodo Based Blended Learning on accounting learning outcomes; (2) there was a difference effect of the high, moderate, and low self regulated learning on accounting learning outcomes; and (3) there was not an interaction between the Edmodo Based Blended Learning and the conventional learning with self regulated learning on accounting learning outcomes.